Utilizing CRISPR-Cas in Tropical Crop Improvement: A Decision Process for Fitting Genome Engineering to Your Species - Joo, Kathleen A.; Muszynski, Michael G.; Kantar, Michael B.; Wang, Ming-Li; He, Xiaoling; Del Valle Echevarria, Angel R. (Frontiers in Genetics, 2021)
Adopting modern gene-editing technologies for trait improvement in agriculture requires important workflow developments, yet these developments are not often discussed. Using tropical crop systems as a case study, we describe a workflow broken down into discrete processes with specific steps and decision points that allow for the practical application of the CRISPR-Cas gene editing platform in a crop of interest. While we present the steps of developing genome-edited plants as sequential, in practice parts can be done in parallel, which are discussed in this perspective. The main processes include (i) understanding the genetic basis of the trait along with having the crop’s genome sequence, (ii) testing and optimization of the editing reagents, development of efficient (iii) tissue culture and (iv) transformation methods, and (v) screening methods to identify edited events with commercial potential. Our goal in this perspective is to help any lab that wishes to implement this powerful, easy-to-use tool in their pipeline, thus aiming to democratize the technology.